The effective use of social media in an effort to increase young voter participation in the 2024 elections - Sumardi, Mar'ah Sholikhah; Suyahman, Suyahman; Fatimah, Siti (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
The purpose of this study is to examine the success of the influence of social media use on the active participation of young voters in the 2024 General Election. The participation of young voters has an essential role in organizing the 2024 Election because they dominate the number of voters. This research was conducted using a qualitative method with data obtained through online questionnaires and literature studies. The data that has been obtained is simplified by removing unnecessary data to facilitate drawing conclusions. From the results of the research, it is known that social media has an important role as a campaign tool to reach young voters. Social media is considered more effective and efficient as a campaign tool compared to conventional methods when viewed from various aspects. Through social media, campaign activities can reach the public at large and can also be utilized as a discussion space that can be accessed by everyone. The freedom to access social media allows for false information (hoaxes) or divisive opinions to emerge. This becomes an arena for the community to be able to think critically in choosing which information to accept and which not. However, the results show that social media still has a big impact on increasing the number of young voters. Another impact is that young voters show their attitude towards their choices and also participate in monitoring the continuity of the 2024 Election